A colorimetric and fluorescence dual-signal determination for iron (II) and H2O2 in food based on sulfur quantum dots. (1st January 2022) - Lu, Changfang; Wang, Yi; Xu, Bingyi; Zhang, Wei; Xie, Yue; Chen, Yinyin; Wang, Lizhi; Wang, Xianxiang
Highlights: The effects of iron (II) and H2 O2 on fluorescence and color of SQDs were explored. A new dual-mode (colorimetric and fluorometric) determination of iron (II) and H2 O2 was established. Abstract: A colorimetric and fluorescence dual-signal method based on sulfur quantum dots (SQDs) was established for determination of iron (II) (Fe 2+ ) and H2 O2 in foods. Due to the complexation of Fe 2+ with SQD, Fe 2+ can cause fluorescence quenching of SQDs, and the color of the mixed solution changed from light yellow to deep green. By use of Fenton reaction, H2 O2 can restore the quenched fluorescence of SQDs, and the color of the mixture changed from green to colorless. The concentration of Fe 2+ and H2 O2 has a good linear relationship with the fluorescence intensity and absorbance in the range of 2.5–55 μM and 1.25–500 μM, and the detection limits were 1.41 μM and 0.54 μM, respectively. For determination of H2 O2, the linear ranges were 1.17–1.97 mM and 0.867–1.50 mM, and the detection limits were 0.03 μM and 0.06 μM, respectively.